2011
DOI: 10.1073/pnas.1012053108
|View full text |Cite
|
Sign up to set email alerts
|

Geminin promotes neural fate acquisition of embryonic stem cells by maintaining chromatin in an accessible and hyperacetylated state

Abstract: Formation of the complex vertebrate nervous system begins when pluripotent cells of the early embryo are directed to acquire a neural fate. Although cell intrinsic controls play an important role in this process, the molecular nature of this regulation is not well defined. Here we assessed the role for Geminin, a nuclear protein expressed in embryonic cells, during neural fate acquisition from mouse embryonic stem (ES) cells. Whereas Geminin knockdown does not affect the ability of ES cells to maintain or exit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 34 publications
8
82
1
Order By: Relevance
“…The levels of trimethylated lysine 27 of H3 (H3K27me3) also remained unchanged (Supplemental Figure 4J). These results suggest that suppression of FoxO3-directed transcription by geminin does not involve the indicated histone modifications as previously reported (39). The acetyl-FKHR antibody, originally developed for detection of FoxO1 acetylation on K259, K262, and K271 residues, has been found to recognize acetyl-FoxO3 as well (6), apparently due to the fact that these lysine residues are highly conserved in these FoxO family members.…”
Section: Geminin Suppresses Dicer Expression Via Coupling Of Hdac3 Tosupporting
confidence: 59%
See 1 more Smart Citation
“…The levels of trimethylated lysine 27 of H3 (H3K27me3) also remained unchanged (Supplemental Figure 4J). These results suggest that suppression of FoxO3-directed transcription by geminin does not involve the indicated histone modifications as previously reported (39). The acetyl-FKHR antibody, originally developed for detection of FoxO1 acetylation on K259, K262, and K271 residues, has been found to recognize acetyl-FoxO3 as well (6), apparently due to the fact that these lysine residues are highly conserved in these FoxO family members.…”
Section: Geminin Suppresses Dicer Expression Via Coupling Of Hdac3 Tosupporting
confidence: 59%
“…Together, these data indicate that geminin facilitates the deacetylation of FoxO3 by recruiting HDAC3, thereby suppressing the transcriptional activity of FoxO3. High levels of geminin have been proposed as facilitating hyperacetylation of histones, therefore increasing chromatin accessibility when regulating neural gene expression in mouse embryonic stem cells (39). This prompted us to investigate whether the action of geminin on FoxO3-mediated transcription may also involve a direct modification of histones at the FoxO3 target promoters.…”
Section: Geminin Suppresses Dicer Expression Via Coupling Of Hdac3 Tomentioning
confidence: 99%
“…36 Geminin directly interacts with the chromatin remodeler Brg1, 37 an association that has clear implications for terminal differentiation. 9,38 By maintaining chromatin in an accessible hyperacetylated state, 39 the abundance of geminin Geminin is also present at high levels in both the nucleus and cytoplasm of malignant trophoblast cells of choriocarcinomas with enlarged nuclei. total DNa, blue.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently revealed that Gemini is involved in restraining the mesodermal and endodermal lineage commitment in the early Xenopus embryo by recruiting the Polycomb-group protein Ezh2 is necessary [55]. However, during development of the ectoderm, Geminin promotes the neural fate acquisition of mouse ESCs by maintaining the chromatin of lineage-specific genes in an accessible and hyper acetylated state [56]. These results suggest that the transcription factors might have distinct roles in regulating chromatin signatures at different enhancers.…”
Section: Esc Factors and Epigenetic Marksmentioning
confidence: 75%